The Quality of Work Life of the Faculty - Dr. Rovilyn Katalbas - Dagondon (IJRDO- Journal of Educational Research, 2019)
Quality of work life (QWL) is the favorable and unfavorable outlook of the employees towards his job and organization (Ananth and Bhat, 2015). It is one of the interventions used by human resource practitioners to motivate their people to improve performance and achieve organizational goals. This study was conducted to determine the quality of work life of the faculty in the state universities through the use of a quantitative research method with a total of 260 respondents. Based on the findings of the study, the majority of the respondents towards the quality of work life of the faculty was rated as moderate extent. However, the facilities got the lowest weighted mean. Hence, there is a need for the improvement on the facilities in order to increase the productivity of the faculty in achieving academic excellence and to continually attract and retain them to work in the state universities.